The Effect of Acupressure on Fasting Blood Glucose Levels in Clients with Type II Diabetes Mellitus - Wekoadi, Galih Mahendra; Arwani, Arwani; Widigdo, Dwi Ari Murti (Riviera Publishing, 2024)
Diabetes mellitus is a? disease that has a characteristic signs? in the from of an increase in glucose levels exceeding normal range . The prevalence of diabetes mellitus is increasing significantly. Currently, the management? of diet, exercise and use therapy pharmacological therapy are option in the management of diabetes mellitus. In addition to these therapies, there are complementary therapies such as acupressure. The purpose of this study was to prove the acupressure intervention in influencing fasting blood glucose levels. This research was a quasi- experimental study with a nonequivalent control group design with pre – test post – test. This study had 38 respondents? whi were devided into 2 groups and were taken using a consecutive sampling techniques. This study was conducted from April 7th 2021 – May 9th 2021. The pre – test and post -test difference test used the wilcoxone test. The diferent test between groups used Man – Whitney test and Independent – t test. Study This showed that there were significant differences? before and after treatment in all groups p = < 0.05. The results of the post-test differences between groups also showed p = 0.012 which shows that there are meaningful differences? between post-tests in groups intervention and control groups. Complementary therapy in the form of proven acupressure can decrease fasting blood glucose in type II diabetes mellitus patients, and complementary therapy in the form of acupressure can used for decrease fasting blood glucose levels in type II diabetes mellitus patients.